Brain Drain - Akram Malik (Journal of University Medical & Dental College, 2020)
Human capital flight most commonly known as Brain Drain is large scale emigration of large group of individuals which have technical skills and knowledge. There are many reasons like lack of opportunities, political instability, economic depression, health risks, law and order situation, and most importantly injustice in the society.